Persistent Voltage Control of a Wind Turbine-Driven Isolated Multiphase Induction Machine - Ben Sliemene, Marwa; Khlifi, Mohamed Arbi (Engineering, Technology & Applied Science Research, 2023)
The growing concern about the energy crisis and environmental protection has caused a growing interest in wind power generation systems. Researchers and engineers urgently need to create new multiphase induction machines for the production of wind energy, since they are essential parts of wind turbines. This study offers control and stability analysis of a multiphase induction machine based on the entropy stability requirements for its linearized model. The generated model was used to assess the on-load properties of the multiphase induction machine and calculate its steady-state parameters under each operating circumstance. According to the analysis, the eigenvalues depend on the machine parameters, with the excitation capacitance and speed variation being the most important. Stabilization of the multiphase induction machine is the main focus of the singular values, which vary according to its variables. The simulated results include an examination of a multiphase induction machine steady state for voltage build-up at various types of load.